Clinical characteristics and outcomes of invasive and non‐invasive fusariosis in South Korea. Issue 3 (20th November 2022) - Park, Hyejin; Bae, Seongman; Kim, Min Jae; Chong, Yong Pil; Kim, Sung‐Han; Choi, Sang‐Ho; Lee, Sang‐Oh; Kim, Yang Soo; Jung, Jiwon
Abstract: Background: Invasive fusariosis mainly affects immunocompromised patients including haematopoietic stem cell transplant recipients and those with haematologic malignancy. There are limited studies on invasive fusariosis in the Asia‐Pacific region. Objective: To describe the clinical characteristics and outcomes of invasive and non‐invasive fusariosis in South Korea. Patients/Methods: From 2005 to 2020, patients with fusariosis who met the revised European Organisation for Research and Treatment of Cancer and the Mycoses Study Group criteria for the definition of proven or probable invasive fusariosis, and those with non‐invasive fusariosis were retrospectively reviewed in a tertiary medical centre in Seoul, South Korea. Results: Overall, 26 and 75 patients had invasive and non‐invasive fusariosis, respectively. Patients with invasive fusariosis commonly had haematologic malignancy (62%), were solid organ transplant recipients (23%), and had a history of immunosuppressant usage (81%). In non‐invasive fusariosis, diabetes mellitus (27%) and solid cancer (20%) were common underlying conditions. Disseminated fusariosis (54%) and invasive pulmonary disease (23%) were the most common clinical manifestations of invasive fusariosis; skin infection (48%) and keratitis (27%) were the most common manifestations of non‐invasive fusariosis. Twenty‐eight‐day and in‐hospital mortalities were high in invasive fusariosis (40% and 52%, respectively). In multivariate analysis, invasive fusariosis (adjusted odds ratio, 9.6; 95% confidence interval 1.3–70.8; p  = .03) was an independent risk factor for 28‐day mortality. Conclusions: Patients with invasive fusariosis were frequently immunocompromised, and more than half had disseminated fusariosis. Invasive fusariosis was associated with poor prognosis.